The Presence of Tobacco Mosaic Virus in the Compost Extract of Cigar Tobacco Debris - WAHYUNI, WIWIEK SRI; HANAPI, MUHAMMAD; HARTANA, IGNASIUS (HAYATI Journal of Biosciences, 2009)
Tobacco mosaic virus (TMV) is resistance to high temperature and able to survive over 10 years on dried leaves, and plant debris is considered as source of inoculums of TMV in the field. In order to inactivate TMV, TMV-infected cigar tobacco debris was composted at starting temperature of 50 ÂºC for two to three days; however, TMV was still infective in the extract compost. If a half leaf cigar tobacco ’H877’ was inoculated with compost extract, the symptoms appeared as a necrotic local lesion (NLL) and did not develop systemic lesions. The dilution end point of TMV in extract compost was 10-3. The number of lesion was higher in the glasshouse with average daylight temperature of 32 ÂºC than in the field with average daylight temperature of 29-30 ÂºC. The number NLL was lower and NLL size seemed to be smaller on the first and second inoculated leaves with extract than that of on the first and second inoculated leaves with TMV inoculums. There was a delay of time about 58-106 hours after inoculation of NLL from extract compost inoculums to appear than those of from TMV inoculums. These could be happened because of mineral nutrients of compost and also the temperature of maintaining tobacco plant which inhibited the infections, and of a thermal composting process which destroyed some TMV particles, particularly degraded itâ€™s coat protein. Key words: TMV, extract water compost, cigar tobacco debris